"There Will Be an End, But We Don't Know When": Preserving Diverse COVID-19 Pandemic Experiences Through Oral History. Issue 2 (June 2022) - Nyitray, Kristen J.; Reijerkerk, Dana; Kretz, Chris
In March 2020, Stony Brook University Libraries began documenting campus communications and the events locally unfolding as the COVID-19 pandemic emerged across the world. These efforts evolved into a larger rapid-response collecting project planned and managed remotely. Documenting COVID-19: Stony Brook University Experiences was developed to preserve institutional history and experiences. With a collecting scope of personal narratives, photographs, and oral histories, the initiative presented new opportunities and challenges for Stony Brook University Libraries. This study discusses the oral history methods for the project from concept to implementation. It describes the planning and managing processes for the oral histories and considers the ethics of recording trauma experiences contemporaneously during the pandemic. The authors offer practical guidance for developing and processing a rapid-response collection of oral histories in a remote environment.